PENINGKATAN KEMAMPUAN MENGENAL HURUF MELALUI MEDIA DADU HURUF PINTAR PADA ANAK USIA (4-5 TAHUN) DI TK MARDISIWI - Iisnaini, Iisnaini; A. Zulkarnain Ali, A. Zulkarnain Ali; Wedya Puspita, Wedya Puspita (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Early childhood (0–6 years) is a critical period in physical, mental, emotional, social, and intellectual development, thus requiring appropriate attention and education from an early age, both formal and non-formal. Education has various definitions depending on the perspective, and one form of early childhood education is through Kindergarten (TK). Language is an important aspect in child development, especially the ability to recognize letters as a foundation for reading and writing skills. To support this, teachers need to use learning methods and media that are interesting and appropriate to the child's development. This research was conducted at Mardisiwi Kindergarten, Banyuwangi because it was found that children still had difficulty recognizing letters due to conventional learning methods. Therefore, the researcher introduced the Smart Letter Dice media to improve children's letter recognition. In this study, the researcher used a classroom action research method with four stages of data analysis: planning, implementation, observation, and reflection. In this study, two data were generated, namely qualitative data and quantitative data. The formulation of the problem in this study is: Can the Smart Letter Dice media improve children's letter recognition skills at Mardisiwi Kindergarten? This study aims to determine to what extent smart letter dice media can improve the ability to recognize letters in early childhood and how it can be applied in the teaching and learning process in the classroom.